Interfacial microstructure evolution and shear strength of MWCNTs-reinforced Sn-1.0Ag-0.5Cu (SAC105) composite solder interconnects on plain Cu and ENIAg surface finish - Dele-Afolabi, T. T.; M. A., Azmah Hanim; K., Vidyatharran; K. A., Matori; O., Saliza Azlina; R., Calin (Springer Link, 2022)
The combined effect of MWCNTs (multi-walled carbon nanotubes) and ENIAg (Electroless Nickel Immersion Silver) surface finish on the formation of interfacial microstructure and shear strength of the Sn-1.0Ag-0.5Cu (SAC105) solder was investigated in this study. Plain and composite solders (SAC-xCNT; x = 0, 0.01, 0.05 and 0.1wt%) were successfully synthesized through the powdermetallurgy route and afterwards soldered on the ENIAg surface finish and plain Cu substrates. Detailed analysis of the microstructure revealed the formation of the Cu6Sn5 IMC at the SAC solder/Cu substrate interface of the SAC-xCNT/Cu solder interconnects. Whereas, the Ni3Sn4 IMC and (Cu,Ni)6Sn5 IMC appeared at the SAC solder/ENIAg substrate interface of the SAC-xCNT/ENIAg. The MWCNTs-reinforced SAC composite solder interconnects exhibited thinner interfacial IMC layer thicknesses relative to the plain counterparts for both substrates used. Given the prospects of the ENIAg as a reliable surface finishmaterial, the SAC-xCNT/ENIAg exhibited IMC thickness valueswithin the range of 2.98–2.65 lm as compared to the 5.23–3.61 lm demonstrated by the SACxCNT/Cu. Overall, the strengthening capacity of the MWCNTs was well-defined in both sample grades, with the SAC-0.05CNT/Cu and SAC-0.05CNT/ENIAg exhibiting the highest shear strength values of 10.23 MPa and 11.14 MPa, respectively.